The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/stem.2238
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord-derived mesenchymal stem cells elicit macrophages into an anti-inflammatory phenotype to alleviate insulin resistance in type 2 diabetic rats

Abstract: Insulin resistance, a major characteristic of type 2 diabetes (T2D), is closely associated with adipose tissue macrophages (ATMs) that induce chronic low-grade inflammation. Recently, mesenchymal stem cells (MSCs) have been identified in alleviation of insulin resistance. However, the underlying mechanism still remains elusive. Thus, we aimed to investigate whether the effect of MSCs on insulin resistance was related to macrophages phenotypes in adipose tissues of T2D rats. In this study, human umbilical cord-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 45 publications
6
112
0
1
Order By: Relevance
“…Studies involving MSC transplantation in mouse models of macrophage hyperactivity, such as sepsis and zymosan induced peritonitis, disease amelioration with concomitant macrophage reprogramming was observed3940. Similarly, MSC transplantation in a rat model of diabetes resulted in conversion of adipose tissue associated macrophages to a M2 phenotype alongside correction of other disease parameters18. In all the above models, MSCs possibly interacted with inflammatory macrophages which were predominant in the disease scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving MSC transplantation in mouse models of macrophage hyperactivity, such as sepsis and zymosan induced peritonitis, disease amelioration with concomitant macrophage reprogramming was observed3940. Similarly, MSC transplantation in a rat model of diabetes resulted in conversion of adipose tissue associated macrophages to a M2 phenotype alongside correction of other disease parameters18. In all the above models, MSCs possibly interacted with inflammatory macrophages which were predominant in the disease scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of alternatively activated macrophages have conferred protection in inflammatory diseases such as Type I diabetes, indicating their decisive roles in reprogramming host inflammation16. Further, few very recent evidences indicate an increased recruitment of anti-inflammatory macrophages in in vivo models of MSC transplantation were regeneration and repair was noted1718. Macrophages exist in a spectrum of functional states and exaggerated anti-inflammatory (M2) or inflammatory (M1) macrophage functional states are associated with distinct pathologies.…”
mentioning
confidence: 99%
“…Further analysis showed that M1-stimulated UC-MSCs increased expression of IL-6. IL-6 upregulated IL4R expression, promoted phosphorylation of STAT6 in macrophages, and ultimately reprogrammed macrophages into an M2 phenotype [67]. In addition, conditioned media from adipose tissue-derived MSCs reversed insulin resistance in insulin-resistant cell models, as evidenced by restored insulin and stimulated glucose uptake, via up-regulation of the GLUT4 gene and reductions in IL-6 and plasminogen activator inhibitor-1 (PAI-1) gene expression [68].…”
Section: Molecular Mechanism Of Action Of Mscsmentioning
confidence: 99%
“…Therefore, huMSCs are ideal seed cells in tissue engineering 7 . Furthermore, numerous studies have explored huMSC treatments and the effect on various conditions, such as acute lung injury, diabetes with insulin resistance and Alzheimer’s disease 811 .…”
Section: Introductionmentioning
confidence: 99%